Sentir-penser avec la Terre: l'écologie au-delà de l'Occident - Escobar, Arturo; Andrade Pérez, Roberto; Bonvalot, Anne-Laure; Bordai, Ella; Bourguignon, Claude; Colin, Philippe; Bednik, Anna (Éditions du Seuil, 2018)
"Les avancées récentes de l'anthropologie l'ont amplement démontré : la partition nature/culture qui fonde l'ontologie moderne occidentale et qui s'est imposée partout n'est pas la seule façon d'être au monde, encore moins la forme ultime de la civilisation. Un tel dualisme, qui sépare corps et esprit, émotion et raison, sauvage et civilisé, acteur et chercheur, humains et autres qu'humains, nous empêche de nous vivre comme partie du monde et nous conduit à le détruire. Dès lors, le projet émancipateur ne saurait se limiter à " changer le monde ". Il s'agit aujourd'hui de changer de monde. Des mouvements indigènes du Sud aux "zones à défendre" (ZAD) du Nord, les conflits politiques renvoient à des visions divergentes quant à la composition du monde et aux façons d'en prendre soin. Autrement dit, à un conflit ontologique. Comment, à l'heure de la crise écologique et face à l'échec de la mondialisation, penser cette dimension ontologique de la politique? Comment engager notre transition, en dialogue avec luttes des peuples non-occidentaux et les cosmologies non-modernes, pour habiter en conscience le plurivers, ce monde des mondes qu'est notre planète?"– Résumé de l'éditeur.
Section: 225 pages : illustrations ; 19 cm.
Keywords: anthropologie; approches et analyses; capitalisme; com5170; cours; crise écologique; discipline; environnement; justice sociale; ontologie; premier cycle; sciences humaines; système colonial; systèmes d'oppressions; thématiques; écologie

Climate change, colonialism, and women’s well-being in Canada: What is to be done? - Williams, Lewis (Canadian Journal of Public Health, 2018)
The impacts of accelerating climate change across Canada are unequally distributed between populations and regions. Emerging evidence shows climate change and resultant policies to be worsening gendered social and economic inequities between women and men, with women’s participation largely absent in climate change research and decision-making. These dynamics are resulting in negative impacts for women’s well-being, with Indigenous and historically marginalized women at increased risk of experiencing health inequities as a result of climate change. To date, public health discourse has largely failed to incorporate gender as a key determinant of health in discussions of climate change impacts on populations. Paralleling this lack of development, the entangled relationship between climate and colonialism tends to be subsumed under the term “Aboriginality” within health determinants discourse. This commentary on gender and climate change in Canada is framed within a radical intersectional approach as an alternative course of public health analysis and action aimed at addressing resulting health and power inequities. Following an overview of evidence regarding the gendered impacts of climate change on women’s work, roles, agency, and well-being, several possible public health action areas on climate change and gender are highlighted as necessary components for resilient communities capable of meeting contemporary challenges.
Keywords: amériques; approches et analyses; canada; changements climatiques; environnement; intersectionnalité; invisibilisation des femmes autochtones; projet charge mentale; régions géographiques; santé; santé des femmes*; sexisme; système colonial; systèmes d'oppressions; thématiques